Implementasi Metode SAW dalam Penilaian Kinerja Tenaga Harian Lepas - Khairil; Hari Aspriyono (Universitas Negeri Gorontalo, 2021)
The performance assessment of Civil Servants at the Bengkulu Province Communication, Informatics, and Statistics Service (Diskominkotik) process has utilized an e-performance application. However, the assessment of daily workers' performance is not included, which means evaluating their performance and competence would take a long time. This study aims to determine daily workers to get the best performance rewards using the Simple Additive Weighting (SAW) method. The research method used was the waterfall method, supported by data from observations, interviews, and questionnaires. Unified Modeling Language (UML) was used to analyze and design the system and in the coding stage, Microsoft Visual Studio 2010 software connected to a MySQL database was used, and in the testing stage, a Black-box testing approach was employed. The results showed that the implementation of the SAW method in the decision support system application could speed up the process of evaluating the performance of daily workers at Bengkulu Province Diskominkotik. Furthermore, daily workers’ performance appraisal became more objective because it involves the participation of many parties so that the results of the best daily worker employee performance appraisal can be accepted by various parties.